Numbered Head Together Technique on Improving Students’ Reading Comprehension - Fahmi Risnaldi; Bustami Usman; Diana Achmad (Research in English and Education Journal, 2017)
This study aims at investigating the impacts of the implementation of Numbered Heads Together technique perceived by the students on their reading comprehension and the impacts of the implementation of Numbered Heads Together technique perceived by the teacher on her students and the difficulties. Descriptive qualitative study design was undertaken by using purposive sampling. The instruments of this study were questionnaire items and interview guide. The collected data were analyzed by presenting them in the form of narration and three steps proposed by Miles and Huberman. The result of this study showed that the implementation of Numbered Heads Together technique gave positive impacts perceived by the students and the teacher. Their enthusiasm in learning can be higher, easier in accomplishing the difficult questions, more interested in group working, and easier in accomplishing the difficult questions. Thus, Numbered Heads Together technique can be used by the English teacher as one of the alternative teaching techniques in English particularly teaching reading in EFL classroom.